Classroom Management in EFL Speaking Class: Strategies and Challenges - Safrul Muluk; Habiburrahim Habiburrahim; Teuku Zulfikar; Saiful Akmal; Nasriyanti Nasriyanti; Muhammad Safwan Safrul (IJEE (Indonesian Journal of English Education), 2021)
ABSTRACTThis research was designed to investigate the strategies used and challenges faced by lecturers in managing EFL speaking classes. The researchers used both classroom observation and semi-structured interviews in collecting the data. The participants of this research were three EFL lecturers teaching English Speaking classes at the English Department of Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia. These lecturers were selected purposively; all of them were those assigned to teach the speaking class. Insights of the lecturers on their experiences in managing speaking classes were investigated to examine strategies and challenges they faced. The findings suggest that the lecturers utilized several strategies such as setting the classroom, determining seating arrangements, fostering discipline, applying certain speaking activities, and providing interesting topics to discuss. The data also indicated that the lecturers faced challenges in managing their teaching. Issues such as lack of equipment or teaching media to support speaking activities, students’ lacked self-confidence, and lack of vocabulary were among the challenges faced by the lecturers.  ABSTRAKPenelitian ini bertujuan mendapat informasi tentang strategi dan tantangan yang dihadapi dosen di dalam mengelola kelas. Metode pengumpulan data yang digunakan adalah observasi dan wawancara semi-terstruktur. Sumber data atau partisipan dalam penelitian ini adalah 3 dosen yang mengajar kelas Speaking di Prodi Pendidikan Bahasa Inggris, UIN Ar-Raniry Banda Aceh. Para partisipan itu direkrut mengunakan teknik purposive sampling, dimana partisipan yang terlibat adalah yang sudah mengajar speaking selama beberapa semester. Hasil obssrevasi dan wawancara diperoleh informasi bahwa terdapat beberapa strategi dosen di dalam mengelola kelas, diantaranya: menyusun tempat duduk sedimikian rupa, menegakkan disiplin, mengunakan berbagai teknik pembelajaran speaking, dan memberikan topik yang menarik untuk didiskusikan. Penelitian ini juga memperoleh beberapa temuan yang berhubungan dengan tantangan dosen, diantaranya, tidak mencukupi fasilitas yang memadai yang dapat mendukung aktivitas pembelajaran speaking, kurangnya rasa percaya diri dari mahasiswa itu sendiri, dan tidak memadainya kosa kata yang dikuasai mahasiswa juga merupakan tantangan tersendiri dalam pengelolaan kelas speaking.